The clinical and immunological efficacy of a mouth rinse containing green tea and Salvadora Persica L. in patients with dental biofilm-induced gingivitis (randomized clinical trial) - Saeed, Aliaa; Abdul Aziz, Maha; Al-Waeli, Haider A (Journal of Baghdad College of Dentistry, 2026)
Background: Dental biofilm-induced gingivitis is an inflammatory condition resulting from the interaction between dental plaque and the host's immune-inflammatory response at the site level. Objective: examine the anti-plaque and anti-inflammatory properties of GT/SP (Green Tea/Salvadora Persica Linn) mouthwash in individuals with dental biofilm-induced gingivitis. Moreover, a study was conducted to compare the effects of GT/SP with those of CHX (Chlorhexidine) and placebo mouthwashes, and to anticipate outcomes of plaque control together with proposing cut-off points for the predictors on the profile of the salivary biomarker IL-6. Material and Methods: The clinical trial was conducted using a randomized, double-blinded, and parallel design. A total of sixty patients diagnosed with generalized biofilm-induced gingivitis were randomly divided into three groups for the administration of mouthwashes: GT/SP, CHX, and placebo. The study lasted for one month, during which participants used 15 milliliters of GT/SP mouthwash formulation, CHX (0.12%), or a placebo, twice daily. Each individual had two assessments, one at the beginning and another after one month.  Before and after each participant’s mouthwash usage, the Patient's plaque level and bleeding on probing were   assessed. The quantification of the Salivary IL-6 in saliva was assayed using enzyme-linked immunoassay (ELISA). Results: A significant decrease in salivary interleukin-6 was observed in all three groups. However, there was no significant difference between the GT/SP and CHX groups in intergroup comparisons at second visits (P>0.05). In addition, all treatments significantly decreased the build-up of Plaque, with the mouthwash containing Green Tea (GT) and Salvadora Persica Linn (SP) having a more pronounced effect compared to the other two treatments. Conclusion:  Mouthwash with GT/SP exhibited both anti-plaque and anti-inflammatory properties. The above findings suggest that GT/SP     may have positive effects in treating dental biofilm-induced gingivitis, making   GT/SP a suitable alternative to chlorhexidine.